Swedish cognitive tests (synthetic data) - Kokkinakis, Dimitrios (University of Gothenburg, 2026)
Swedish Cognitive Tests refers to a collection of neuropsychological assessments commonly used in Sweden to evaluate cognitive functioning, particularly in clinical settings such as dementia or neurological evaluations. This group includes tests such as SVF (Semantic Verbal Fluency), FAS (phonemic verbal fluency), and the BNT (Boston Naming Test - confrontation naming). Other tests, such as Cookie Theft and Trip to Stockholm, are also used and assess, among other things, language production, speech fluency, and sentence structure. These assessments measure different aspects of language and executive functioning, including the ability to rapidly generate words within a semantic category, produce words beginning with specific letters, and name pictured objects. Together with other tests such as the Stroop Test, and the Trail Making Test A and B , these tests provide a broad overview of an individual’s linguistic and cognitive abilities.

Svenska kognitiva tester syftar på en samling neuropsykologiska test som används i Sverige för att bedöma olika kognitiva funktioner, ofta vid utredning av exempelvis demens eller andra neurologiska tillstånd. Inom detta tema ingår bland annat tester som SVF (semantiskt ordflödestest), FAS (fonologiskt ordflödestest) och BNT (Boston Naming Test - konfrontationsbenämning). Andra tester, som Kakstölden och Resa till Stockholm, förekommer också och undersöker bland annat språkproduktion, talets flyt och meningsbyggnad. Dessa tester mäter olika aspekter av språk och exekutiva funktioner, såsom förmågan att snabbt generera ord inom en kategori, producera ord som börjar på specifika bokstäver samt förmågan att namnge bilder av objekt. Tillsammans med andra tester, såsom Stroop Test, och Trail Making Test A och B, ger de en bred bild av individens språkliga och kognitiva förmåga.
Svenska kognitiva tester (syntetiska data)
Keywords: Language Technology (Computational Linguistics); cognitive tests; neuropsychology; language function; executive function; verbal fluency; naming test; confrontation test; SVF; FAS; BNT; MMSE; planning task; corpus; Natural Language Processing; Språkbehandling och datorlingvistik